Manajemen Produksi Home Industry Perspektif Ekonomi Islam - Slamet Akhmadi; Istiqomah Istiqomah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
Home Industry Mega Sandra is a furniture business in Buntu, Kroya, Cilacap that utilizes raw materials of teak, jackfruit wood, and laban wood in making furniture. According to T. Hani Handoko management production is an optimal management efforts in the use of resources in the process of transforming raw materials and labor into various products or services. Management production is also the process of making products or providing services, creating and operating systems and structures through the people involved in them. Management production is also a very important role in the process of making furniture. The purpose of this research is to find out what management production is used by Mega Sandra's Home Industry in the perspective of Islamic economics. Based on the results of research conducted by the author, it can be concluded that the Mega Sandra home industry has run its production management process in accordance with the perspective of Islamic economics. About natural resources (raw materials), human resources (labor) in accordance with Islamic sharia.